A patient with porocarcinoma of the lower extremity and lung metastasis: a rare case report - Zein, Ahmad Fariz Malvi Zamzam; Luthfi, Mohamad; Putro, Widyatmiko Arifin; Nurbaiti, Nurbaiti (Medicine and Pharmacy Reports, 2022)
Background. Porocarcinoma is a rare cancer of the developing sweat glands. It often occurs in older adults and frequently affects the head, neck, and extremities. We report a rare case of metastatic porocarcinoma with intriguing approach of the diagnosis and management due to limited resource setting. Case Report. A 60-year-old man with a history of type 2 diabetes mellitus presented with nodules on the left foot with no palpable lymph node. A chest radiograph revealed multiple coin lesions and histopathological findings were suggestive for porocarcinoma. We assessed the case as a metastatic porocarcinoma in a patient with uncontrolled type 2 diabetes mellitus. Surgery was performed in the initial phase of treatment, consisting of below-knee amputation. The patient refused the planned chemotherapy in the referral hospital and then underwent other modalities of palliative care. He passed away eleven months after the initial diagnosis. Conclusions. Metastatic porocarcinoma is a rare oncological case with a challenging approach of the diagnosis and management. High awareness of clinical clues in rare cancer is needed for early diagnosis and prompt treatment, especially in limited resource settings.